The Influence of the Penggerak School Program and Teacher’s Work Motivation on the Quality of Primary School Learning - Winarti, Mimin; Fitria, Happy; Mahasir, Mahasir (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
This research aims to determine and describe the influence of Penggerak school programs and teacher work motivation on the quality of elementary school learning in Lempuing Jaya District partially and simultaneously. This research method is quantitative correlational, with the research population being all teachers at SD Negeri 2 Lubuk Seberuk and SD Negeri 1 Lubuk Makmur, Lempuing Jaya District, totaling 55 teachers, all used as the research sample. Data was collected by documentation and questionnaires and analyzed with descriptive statistics and analytical hypotheses using simple regression and multiple regression with the help of SPSS 26. The results of this study show that: (1) there is a significant influence of the Penggerak school program on the quality of learning, (2) there is a significant influence of teacher work motivation on the quality of learning, (3) there is a significant influence of Penggerak school programs and teacher work motivation on the quality of elementary school learning in Lempuing Jaya District.